Genomic exploration of Cepaea species: from phylogeography to phenotypic variation - Chowdhury, Mehrab (2025)
The land snail genus Cepaea has long served as a model system for understanding the evolutionary forces shaping phenotypic diversity. This thesis builds on that rich history by integrating genomic, mitochondrial, and phenotypic analyses to uncover new insights into the evolutionary history, genetic architecture, and phenotypic variation of Cepaea hortensis and Cepaea nemoralis.